2013
DOI: 10.5935/1676-4285.20134263
|View full text |Cite
|
Sign up to set email alerts
|

Attention to the parturient adolescent: access and reception - a descriptive study

Abstract: Aim: To analyze the access and reception of adolescent mothers in the parturition stage in obstetrics emergencies. Method: This is a descriptive study, with data collected through the interviewing and observation of twelve adolescent mothers, in the Sector of Obstetrics in a tertiary hospital of the public hospital network of the municipality of Fortaleza, Brazil. Results: The first category was the access that adolescent mothers had to a hospital unit, including the journeys that they made and the physical st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
0
1
0
1
Order By: Relevance
“…The excessive occupation of obstetric beds in macroregion I, due to its concentration of high-risk care services, has as a consequence the displacement of women residing in other municipalities 6 . On the other hand, Silva et al 19 found that most users assisted in the healthcare network of Recife lived outside the capital. This finding shows the breakdown of the obstetric care network in Pernambuco, leading to the pilgrimage of women in search of a suitable place for delivery, a fact also observed in another study 20 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The excessive occupation of obstetric beds in macroregion I, due to its concentration of high-risk care services, has as a consequence the displacement of women residing in other municipalities 6 . On the other hand, Silva et al 19 found that most users assisted in the healthcare network of Recife lived outside the capital. This finding shows the breakdown of the obstetric care network in Pernambuco, leading to the pilgrimage of women in search of a suitable place for delivery, a fact also observed in another study 20 .…”
Section: Discussionmentioning
confidence: 99%
“…A excessiva ocupação de leitos obstétricos na macrorregião I, em razão de sua concentração de serviços de atenção ao alto risco, tem como consequência o deslocamento das mulheres residentes para outros municípios 6 . Por outro lado, Silva et al 19 identificaram que a maioria das usuárias atendidas na rede de saúde do Recife residiam fora da capital, evidenciando a desestruturação da rede de atenção obstétrica em Pernambuco, levando à peregrinação das mulheres em busca de um local adequado para o parto, fato também já observado em outro estudo 20 .…”
Section: Discussionunclassified